The Impact of Alcohol Restriction on Hospital and Emergency Department Service Utilizations in Two Remote Towns in the Kimberley Region of Western Australia - Sun, Wenxing; Jian, Le; Xiao, Jianguo; Akesson, Grant; Somerford, Peter (Frontiers in Public Health, 2019)
Background: In a remote region of Western Australia, Kimberley, residents have nearly twice the State average per capita consumption of alcohol, four and a half times the level of alcohol-related hospitalizations and nearly three times the level of alcohol-related deaths. This study aimed to evaluate the long term effects of alcohol sale restrictions on health service utilization in two remote towns in Kimberley. Methods: Sale of high strength packaged alcohol was restricted in Fitzroy Crossing and Halls Creek since October 2007 and May 2009, respectively. Alcohol-related Emergency Department (ED) attendances and hospitalizations utilized by local residents before and after the intervention between 2003 and 2013 was compared by using yearly rates (/1,000 person-years) and interrupted time series analysis with Autoregressive Integrated Moving Average (ARIMA) modelling. The Western Australia specific aetiological fractions (AAFs) were applied to hospital inpatient data for estimation of the proportion of hospital separations attributable to alcohol. Results: In Fitzroy Crossing, there was a significant reduction of over 40% on rates (/1,000 person-years) of alcohol-related acute hospitalizations (54.2 [95% CI: 53.8-54.7] vs 31.7 [31.4-32.1]) and ED attendances (534.1[532.8-535.5] vs 294.5 [293.5-295.4]). In Halls Creek, there was a significant reduction of over 50% on rates (/1,000 person-years) of alcohol- related acute hospitalizations (17.7 [17.6-17.8] vs 8.0 [7.9-8.1]) and ED attendance (248.4 [247.9-248.9] vs 111.1[110.8-111.5]). Domestic violence and injury related hospitalisation rates were also reduced by over 20% in both towns. Conclusions: The total restriction of selling high strength alcohol through a community driven process has shown to be effective in reducing alcohol-related health service utilization in post-intervention period. Continue monitoring is required to address new emerging issues. Future research on health service utilization related to alcohol by using interrupted time series analysis ARIMA and applying AAFs are recommended for evaluating alcohol-related interventions.